A primer for working with the Spatial Interaction modeling (SpInt) module in the python spatial analysis library (PySAL) - Taylor Oshan (REGION, 2016)
Although spatial interaction modeling is a fundamental technique to many geographic disciplines, relatively little software exists for spatial interaction modeling and for the analysis of flow data. This applies particularly to the realm of free and open source software. As a result, this primer introduces the recently developed spatial interaction modeling (SpInt) module of the python spatial analysis library (PySAL). The underlying conceptual framework of the module is first highlighted, followed by an overview of the main functionality, which will be illustrated using migration data. Finally, some future additions are discussed.
Keywords: 330; migration; transportation; commuting; retail